دراسة التغيرات الزمانية والمكانية لنظام ثنائي أكسيد الكربون في المياه السطحية البحرية المقابلة لمدينة طرطوس (Latakia University Journal -Basic Sciences Series, 2017)
تركز هذا البحث على تحديد التغيرات الزمانية والمكانية لنظام ثنائي أكسيد الكربون في المياه البحرية لمدينة طرطوس في فصلي ربيع وصيف 2015، ومدى تأثره ببعض العوامل الهيدرولوجية للمياه (درجة حرارة وملوحة) وأثر كل ذلك في قيمpH المياه البحرية .بينت النتائج انخفاض قيم الضغط الجزئي لغاز ثنائي أكسيد الكربون في المياه البحرية(PCO2sea) في فصل الصيف مقارنة مع فصل الربيع، الأمر الذي انعكس على قيم التدفق(FCO2)،حيث انطلق غازCO2من المياه باتجاه الهواء في الصيف والعكس في فصل الربيع (0.0632mmol/m²/day و-0.0715mmol/m²/day على التوالي). ساهم انخفاض درجة حرارة وملوحة المياه في فصل الربيع(C 22.707-22.727و37.605-37.765على التوالي)، بالإضافة إلى زيادة النشاط البيولوجي في زيادة امتصاصCO2من المياه مما يؤدي إلى تناقصPCO2sea(409.0- 429.5µatm) مترافقة مع انخفاض تراكيز كل من إجمالي الكربون اللاعضوي (2229.5-2242.5µmol/kg) والقلوية(2588.873-2590.9µmol/kg)، وبالنتيجة تصبح المياه البحرية مستودع لتخزين غاز ثنائي أكسيد الكربون الجوي.أما في فصل الصيف فإن ارتفاع درجة حرارة وملوحة المياه(C28.85-29.60و38.60 38.15-على التوالي) وتناقص النشاط البيولوجي كل ذلك ساهم في انخفاض قيمCO2المنحل وفي ارتفاعPCO2sea(437.5 - 453.5µatm) مترافقة مع زيادة تراكيز كل من إجمالي الكربون اللاعضوي(2267.9 – 2296.0µmol/kg) والقلوية (2739.6 –2741.2µmol/kg)، وبهذا الشكل تكون المياه البحرية مصدر لغاز ثنائي أكسيد الكربون إلى الغلاف الجوي.This research focuses on identifying spatial and temporal variationsof the carbon dioxide system in the surface seawater of Tartouscityduring the period betweenspring and summer 2015.In Addition to the extent influenced by some hydrological properties of water (temperature and salinity) and the impact all of this on the pH of marine water values.The results showed low partial pressure of the carbon dioxide in seawaters (PCO2sea) in the summercompared with spring, which is reflected on the air-sea flux values (FCO2), where CO2 released from surface seawater to the air in summer and incontradiction of that in the spring (0.0632mmol /m²/ day and -0.0715 mmol /m²/day, respectively). In spring, low temperature and salinity of the water (22.707-22.727C and 37.605-37.765‰ respectively), in addition to increased biological activity contributed in increasing the absorption of CO2 from the water.These leading to a decrease PCO2sea (409.0- 429.5μatm) associated with low concentrations of all of the total inorganic carbon (2229.5-2242.5μmol/kg) and total alkalinity (2588.873-2590.9μmol/kg). and as a result the surface sea waters become a reservoir of dioxide carbon atmospheric.In the summer, the rise in temperature and salinity of surface seawater (28.85-29.60Cand38.15-38.60‰, respectively) and reduced biological activity all contributed to the decrease dissolved CO2 values and increase of PCO2sea(437.5 - 453.5μatm) associated with increasing concentrations of each of the total inorganic carbon (2267.9 - 2296.0μmol/kg) and total alkalinity (2739.6 -2741.2μmol/kg).In this way the surfaceseawater is source of carbon dioxide to the atmosphere.